Dampak Penjualan Pakaian Bekas Terhadap Tingkat Pendapatan Pedaganag Di Pasar Pagi Tugu Pahlawan Kota Surabaya - Damianus Tamo Ama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Purpose: The purpose of this study is to analyze the impact of selling used clothes on the level of income of traders at the Tugu Pahlawan Morning Market, Surabaya City. Method: This type of research uses quantitative methods. The research design used was observational analytic with a cross sectional method approach. Respondents were taken by simple random sampling technique with a total of 30 respondents. The independent variable is the sale of used clothes and the dependent variable is the income level of the trader. Statistical test results using a 2 mean pair difference test. Results: The results showed that the income level of traders before selling used clothes was 1,523,833.33 and after selling used clothes was 4,194,500.00. Suggestion: For traders, it is hoped that the results of this study will help traders maintain the quality of their merchandise and be more selective in selling used clothing. For the Faculty of Economics and Business, University of 17 August 1945 Surabaya. The results of this study are expected to be reading material and insight for students about the impact of selling used clothes on the income level of traders. For the Government, it is hoped that the results of this research can become one of the sources of information and contributions to the direction of the policies pursued by the Government. For future researchers, it is hoped that the results of this study can be used as input and basic data for further research.